Counselling of Medical Students a Supportive Tool - Fauzia Qureshi, Zainul Abideen, Nadia Majeed, Tahrim Ansar, Uzma Waseem, Shamsa (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Medical education is one ofthe toughestcourse worldwide in the education system. Medical students have academic and non-academic problems that can influence their academic performance, Aim: To study the effect of counselling and guidance on the academic performance of medical students through students’ perceptions. Study design: Cross sectional Method: The study was conducted on 3rd year MBBS students of Azra Naheed Medical College Lahore, medical students were divided into two groups (A&B) on the basis of their academicperformance during the year 2021-2022 in professional and module examination. A Google form was developed by the authors of thisstudy which consisted of 13 questionsregarding the perception of students about the effect of counselling and guidance onmultiple factors affecting their academic performance. The form was posted in two official WhatsApp groups (A&B) of the class. In group A, students with good performance and high achievers were included andin group B average and failed students were included. Results: The findings show that the 40 students from group A and 42 students from group B responded to the questionnaire. A higher percentage of students belonging to both groupsresponded positively regarding the role of faculty counselling and guidance in hectic medical study schedules, preparation of professional exams, time management, social, domestic, attendanceissues and overall academic performance. 97.5% of students from group A & 100% of students from group B responded positively to question 12 about Career Counselling of medical students in medical colleges, 97.50% correlation was found in both groups. The result showed that students belonging to good academic performance and students who were average & with low academic performance responded positively to support the role of faculty members. Practical implication: Student counselling plays an important role in medical education. This study showed that positive response of medical students towards student counselling and academic guidance. Need of career counselling is also highlighted by students which raises the question of development of student counselling department in every medical institute. Conclusion: It has been found that there is an important role of faculty members in solving the academic &non-academic problems of students. In a recent study, students have recognised the supportive role of faculty members in the improvement of their academic performance through theirguidance and counselling. Keywords: Academic performance, counselling, guidance, faculty members, medical education, student perception